Síntese de 1,2,4-oxadiazóis derivados de 4-tiazolidinonas e arilamidoximas - Martins, Bruna Simões (2012)
The current work reports the incorporation of 4-thiazolidinones to oxadiazolic ring by a simple and effective methodology. Five species of thiazolidinones were synthesized by three component condensation reaction of glycine ester, aldehydes or ketones and mercaptoacetic acid. Different substituent (methyl, ethyl, ciclohexyl, phenyl) were introduced at 2 position of the ring. These compounds were incorporated to oxadiazole scaffold by reaction with arylamidoximes and potassium carbonate using toluene as solvent. It was possible to extend the developed methodology to derivatives of alanine ester, obtaining two new thiazolidinones, which were employed at the synthesis of two representatives oxadiazoles by reaction protocol proposed by this work. The targets heterocycles of this work were rightly synthesized and characterized. Their incorporation was successful, performed in yields of 40-82%, using potassium carbonate, a convenient reagent due to its low cost, easy accessibility and efficiency in the synthesis of 1,2,4-oxadiazoles from ester and arylamidoximes.